HEALTHY LIFESTYLE AND ITS FORMATION AMONG STUDENTS AND YOUNG PEOPLE IN HIGHER EDUCATIONAL INSTITUTIONS - Avezova Guloyim Sattarovna; Nurullayev Bakhtiyor Tulqinboy ugli (Galaxy International Interdisciplinary Research Journal, 2023)
Forming a healthy lifestyle among student youth and involving them in physical education and sports is one of the most urgent problems of today. A healthy lifestyle is a way of life of a person, in which a person understands a set of activities related to maintaining, strengthening and preventing diseases.